(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
This review paper briefly explains the meaning and characteristics of endocrine disrupting compounds (EDCs). EDCs comprise various types of natural and synthetic chemical compounds that can impede the reproductive action of the endocrine system in animals and humans. Further discussion is on bisphenol A (BPA), one of the examples of EDCs that is extensively used in industries nowadays. It acts as a monomer, which is desired in the production of polycarbonate plastics and epoxy resins. BPA later ends up in environmental compartments (air, water, sediment). In spite of this, BPA is not categorized as a persistent compound and it will be degraded either by photolysis or bacteria. It can only exist between three and five days in the environment. The concentration of BPA varies in different locations depending on the temperature, pH, source and time of sampling. BPA has been frequently debated due to its toxicity and carcinogenicity towards animals and humans. This paper also explains several extraction procedures and analytical methods concerning how to identify BPA in either aqueous or solid samples. However, an additional review is needed in respect of how to handle, reduce the level of BPA in the environment and understand the details concerning the existence of BPA